Statistics of Fracture in 3-Point Bending. (November 2019) - Sadhinoch, M; Kampczyk, M; Mulder, R.
Abstract: CrachFEM have a built-in failure probability model. The failure probability can be derived from the scatter of one material batch, next to the deterministic prediction of the CrachFEM failure risk. In this paper a 3-point bending experiment is used to mimic the in-house forming operation of Faurecia and to derive the failure probability. The failure probability of three materials have been determined with a 3-point bending experiment in combination with an optical strain measurement system. A post-processing procedure has been setup for this purpose. Although the three materials are somewhat comparable, the failure probability is different and will reveal whether a material is critical or suitable for the production process.